2020
DOI: 10.1038/s41598-020-69286-3
|View full text |Cite|
|
Sign up to set email alerts
|

Aerosol and surface contamination of SARS-CoV-2 observed in quarantine and isolation care

Abstract: The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) originated in Wuhan, China in late 2019, and its resulting coronavirus disease, COVID-19, was declared a pandemic by the World Health Organization on March 11, 2020. The rapid global spread of COVID-19 represents perhaps the most significant public health emergency in a century. As the pandemic progressed, a continued paucity of evidence on routes of SARS-CoV-2 transmission has resulted in shifting infection prevention and control guideline… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
536
4
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 522 publications
(625 citation statements)
references
References 17 publications
40
536
4
10
Order By: Relevance
“…Indeed, a better understanding of viral resistance to airborne stress is key to estimating infectious risk. Three published studies (103)(104)(105) included viral cultures from air samples, all of which were negative; however, the Santarpia et al study (103) observed indirect signs of viral replication in two of their samples, including a mild cytopathic effect upon microscopic inspection after 3 to 4 days. On the other hand, in two unpublished studies, Santarpia Western blotting to yield interesting results.…”
Section: Air and No-touch Surface Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a better understanding of viral resistance to airborne stress is key to estimating infectious risk. Three published studies (103)(104)(105) included viral cultures from air samples, all of which were negative; however, the Santarpia et al study (103) observed indirect signs of viral replication in two of their samples, including a mild cytopathic effect upon microscopic inspection after 3 to 4 days. On the other hand, in two unpublished studies, Santarpia Western blotting to yield interesting results.…”
Section: Air and No-touch Surface Samplingmentioning
confidence: 99%
“…The premises of this model are based on cumulative data and clinical observations. In light of the positive air and no-touch surface samples found in health care facilities, respiratory SARS-CoV-2 aerosols probably occur, but many of their attributes are yet unknown; studies thus far seem to suggest these aerosols are short-range and dilute with distance (102,103,144). Similarly, epidemiological studies do not support the existence of long-distance aerosol propagation: the four outbreaks most often cited as evidence of airborne transmission (the Washington choir, the Guangzhou restaurant, the Eastern Chinese bus riders, and the Diamond Princess cruise ship) all involved individuals who were in relatively close contact for a prolonged period of time, in an enclosed space, with the presence of enabling factors (e.g., crowdedness, air currents, and poor ventilation).…”
Section: Conclusion: Proposed Modelmentioning
confidence: 99%
“…A study by Van Dormalan et al found that SARS-CoV-2 virus particles remained infectious for 3 h in experimentally generated virus-containing aerosols that mimic the human-generated ones (83). Several studies reported detecting SARS-CoV-2 RNA in the air samples collected from different areas inside the hospitals such as patients' toilet areas, medical staff areas, and public areas prone to crowding (83,88,89). Recently, it was shown that infectious SARS-CoV-2 can be detected in air samples collected 2-4.8 m away from hospitalized COVID-19 patients, supporting the possibility of airborne transmission at least in confined environments (90).…”
Section: Modes Of Sars-cov-2 Transmissionmentioning
confidence: 99%
“…While the importance of asymptomatic transmission was debated early in the pandemic, many studies have affirmed its role in the spread of disease [25][26][27]. Though environmental transmission of SARS-CoV-2 remains a controversial topic, it is plausible that asymptomatic individuals may spread disease through frequent contact with the environment, thus increasing the proportion of virus that is free-living [28]. We acknowledge that mathematical models of epidemics can be limited by "identifiability," which can obfuscate the relative importance of some routes of transmission.…”
Section: Model Descriptionmentioning
confidence: 99%